Prototipe Sistem Peringatan Penumpang Kereta Api Berbasis Mikrokontroler Arduino Uno Atmega 328 - Prawira, Dimas Adi; Darmawan, Bahrul Ilmi; Saputra, Fadli Irnanda (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2019)
Service and convenience are important factors in carrying out modes of transportation, especially railways. As the development of railways in Indonesia is needed in terms of service and comfort. It often happens that passengers who miss the destination station are still problems that must be resolved in the service and comfort of the train facilities. Early warning systems that are still universal using speakers still lack maximum service. From the results of a survey conducted there are still many potential passengers who are worried about being missed by the destination station. In this research, a prototype of an early warning system with a vibrator mounted on the train seat was made when a passenger arrived at the destination station. This tool is able to provide early warning individually, so that people who will arrive at the destination station are not missed. This prototype works using the Arduino Uno Atmega328 microcontroller as its control system. Vibration machine with 53 Hz of vibration. After testing 43 respondents, the average person woke up after being given a vibration of 53 Hz is 4 seconds. Keypad as data input for destination destination code. The light if the passenger is not awakened turns on for 5 minutes. The results of this study are able to help the early warning system work through speakers more leverage